2019
DOI: 10.1083/jcb.201808044
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q biosynthetic proteins assemble in a substrate-dependent manner into domains at ER–mitochondria contacts

Abstract: Coenzyme Q (CoQ) lipids are ancient electron carriers that, in eukaryotes, function in the mitochondrial respiratory chain. In mitochondria, CoQ lipids are built by an inner membrane–associated, multicomponent, biosynthetic pathway via successive steps of isoprenyl tail polymerization, 4-hydroxybenzoate head-to-tail attachment, and head modification, resulting in the production of CoQ. In yeast, we discovered that head-modifying CoQ pathway components selectively colocalize to multiple resolvable domains in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 82 publications
(120 reference statements)
4
87
0
Order By: Relevance
“…(23). Two recent studies demonstrated that mitochondria isolated from yeast lacking COQ10 have a reduced number of CoQ domain puncta (23,24). This is likely due to lower levels of certain Coq polypeptides and partial CoQ synthome destabilization in the coq10Δ mutant (17,19), which was confirmed in this work ( Fig.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…(23). Two recent studies demonstrated that mitochondria isolated from yeast lacking COQ10 have a reduced number of CoQ domain puncta (23,24). This is likely due to lower levels of certain Coq polypeptides and partial CoQ synthome destabilization in the coq10Δ mutant (17,19), which was confirmed in this work ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…When Coq9-yEGFP was used as a marker for CoQ domains, coq11Δ had increased CoQ domain intensity that stemmed from amplified expression of Coq9-yEGFP, although the number of domains was similar to wild type. Mutants lacking essential Coq polypeptides coq1-coq9, or coq10, displayed significantly less Coq9-labeled domains (24). The CoQ synthome stabilization seen in coq11Δ via 2D-BN/SDS-PAGE analyses performed in this work ( Fig.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…While co-immunoprecipitation of the three proteins suggests stable interactions, the large difference in their abundance (Raijman 1976;Cohen, et al 1982;Sonoda and Tatibana 1983;Wang, et al 2019a) raises questions regarding stoichiometry of such complex. Our data, taken together with large differences in abundance of NAGS, CPS1 and OTC, are consistent with clustering of the three proteins at the IMM, similar to enzymes for biosynthesis of coenzyme Q and purines Chan, et al 2015;French, et al 2016;Subramanian, et al 2019) Enzyme clustering provides metabolic advantages without the need for evolution of complimentary protein-protein interfaces (Sweetlove and Fernie 2018). Theoretical modeling and experiments with engineered proteins in E. coli show that clustering of enzymes that catalyze consecutive reactions of a metabolic pathway can increase flux through the pathway by 100-fold; this is achieved through increased local concentrations of enzymes and metabolites in the cluster (Castellana, et al 2014).…”
Section: Distribution Of Nags Cps1 and Otc In Liver Mitochondriasupporting
confidence: 87%